Risk Factors for Central Serous Chorioretinopathy (Review of Epidemiological Studies) - D. R. Agliullin; G. R. Khasanova; E. A. Abdulaeva (Oftalʹmologiâ, 2019)
Central serous chorioretinopathy (CSCR) is a chorioretinal pathology characterized by the development of serous detachment of the neurosensory retina, local or multifocal areas of fluid filtration at the level of retinal pigment epithelium with predominant damage to the macular region. The epidemiology of CSCR in the Russian Federation has not been studied. Some authors believe that there is a tendency for increasement the incidence of CSCR.This article presents the studies results of the influence of various factors on the disease occurrence. CSCR may be associated with various factors, the their contribution to the etiopathogenesis of the disease may be influenced by national and geographical features. All risk factors of CSCR were conditionally divided into chemical (taking different groups of medicines, smoking, alcohol consumption), biological (the presence of somatic or infectious diseases), psychosomatic (stress, sleep disturbance), socio-demographic (gender, age, race, level of education and income). Currently only an increase in the level of corticosteroids in the blood can be considered as a proven risk factor.Numerous epidemiological studies from around the world show different, often conflicting, data. This makes it difficult to develop methods for the prevention of this disease, and dictates the need for descriptive and  analytical epidemiological studies in this direction.